PENGAWASAN PEMUNGUTAN PAJAK SARANG BURUNG WALET DI KECAMATAN TUALANG KABUPATEN SIAK - Hardiyanto, M. Yusuf; Mashur, Dadang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Siak local tax collection is a mandatory contribution from the taxpayer to the regions that are owed by individuals or entities that are enforceable under the laws taxing areas used for the purposes of the area for the prosperity of the people. One of the regional tax is a tax of birds nest. The tax collection in the district of Tualang is technically implemented by UPT Department of Revenue, Finance and Asset Management Regional District of tramp as an officer of a tax collector. However, in its oversight of the taxpayer has not carried out the examination results direct sales, so do not achieve the tax targets have been set.In this study, the concept of the theory used is the theory of supervision put forward Manullang (2008) as a research instrument, which to measure supervision of tax collection of birds nest must be standards and the size of the first, then held the scoring act and act correction if it deviates from the standard ( conditions set). This research uses qualitative descriptive method of data collection techniques include interviews, observation and documentation study.The results showed the supervision of the tax collection of birds nest has not been optimally implemented. Where actions undertaken votes UPT revenue, Finance and Asset Management Sub district Tualang only through examination of documents the taxpayer. Inspection and monitoring of directly against the business or selling their captive birds nests, to identify and assess the tax compliance in carrying out obligations under optimal conditions have not yet in sight.Keywords: Monitoring, Local Tax, Withholding Tax, Tax Payer